Analisis Hukum Persaingan Terhadap Penyelenggaraan BUMN Berdasarkan Konsep Doktrin “Single Economic Entity” - Istiyanti, Erni (Eastasouth Institute, 2024)
The relationship between one company and its subsidiaries or other companies can be referred to as a single economic entity. The lack of freedom of the subsidiary causes the subsidiary to become a single economic entity. The impact of a single economic entity is that the behavior of each subsidiary is considered to be the same. This research aims to examine two things, First, the legal relationship between the parent and subsidiaries with regard to the concept of